Microfluidic devices to monitor water pollution - Mousah, Rasha Khaleel; Zageer, Dheaa Shamekh; Kasar, Khawla Abd el kareem (Plant Science Today, 2024)
Microfluidic devices offer a promising future for monitoring water pollution caused by heavy metals, especially as the world continues to develop and the dangers of pollutants increases. This highlights the importance of developing these devices. These devices operate within the dynamics of fluids and quantify pollutants with numerous advantages, such as high sensitivity and specificity. They can also be integrated with mini sensors alongside analytical techniques. This study provides a brief overview of the types of microfluidic devices, such as polydimethylsiloxane (PDMS) and microfluidic paper-based (µPADs), and their application in pollutant detection. Microfluidic devices are associated with analytical methods such as spectrometric, colorimetric, and electrochemical techniques. Their importance lies in their simple manufacturing, rapid detection capabilities, and portability. Additionally, these devices can be updated to meet current needs in water pollution detection by integrating various analytical methods and enhancing these methods with programs that provide on-site results. There for microfluidics are currently of great importance due to their ease of manufacturing and applicability to various analytical methods, particularly for detecting pollutants in water. Many studies highlight the extraordinary potential of paper-based devices, which are the easiest to manufacture among all microfluidic devices and are not subject to stringent engineering and physical constraints. Most importantly, they can utilize colorimetric detection methods, providing instant results visible to the naked eye. This study demonstrates these advantages and suggests the potential for expanding their applications in medical, environmental, and biological fields.